ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH MAHASISWA DI FAKULTAS EKONOMI UNIVERSITAS KRISTEN INDONESIA - Anggraini, Nenny; Sembiring, Carolina F.; Panjaitan, Robert (Universitas Kristen Indonesia, 2017)
In this globalization era competition among universities to attract students getting tougher. It is therefore universities should further strenghten its marketing strategy, so that they can attract new students to decide to study in the Faculty of Economics, Christian University of Indonesia, Jakarta. This study aims to determine what factors are influencing numbers students in choosing education at Faculty of Economics, Christian University of Indonesia, Jakarta. The number of samples used in this study were 86 people who are students at the Faculty of Economics, Christian University of Indonesia, Jakarta. Sampling performed by the method of proportionate random sampling. Data were collected using questionnaires. Variables Measurement with Likert scale in 5 (five) scale and analysis with Multiple Reggression with dummy variable. The result shows that factors must consider by the student when decided the Economy Faculty of University of Indonesia, Jakarta, are product, cost, promotion, process, people, physical evidence.Keywords: product, cost, promotion,process, people, physical evidence.